Controlling mitochondrial reactive oxygen species production for cell signaling 2 - Mailloux, Ryan J. (Henry Stewart Talks, 2018)
Controlling mitochondrial ROS production (proton leaks, super complex assemblies, and redox switches), Implications of redox switches in controlling mitochondrial ROS signalling